2007
DOI: 10.1007/s11249-007-9220-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Friction

Abstract: The temperature dependence of the kinetic friction between a highly oriented pyrolytic graphite surface and a silicon nitride probe tip has been evaluated through atomic force microscopy measurements performed under an ultra-high vacuum environment over the temperature range 140-750 K. As temperature increases from 140 to 400 K a sharp decrease in friction is observed. A relatively weaker dependence on temperature is observed in the friction measured between 400 and 750 K. Collectively, these results obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
71
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 16 publications
9
71
1
Order By: Relevance
“…Michael et al [1], Theiler et al [2], and Hubner et al [3] compared results of ambient lab air testing with those of test submerged in cryogenic liquids and have shown either no trend or trends of reduced friction at cryogenic temperatures. Recent constant environment macroscale studies of various solid lubricants [4][5][6][7], and atomic-scale studies with terraces of graphite [8] show consistent trends of increased friction with decreased temperature, and the notion of thermally activated friction has been proposed [4,8,9]. Variable temperature experiments conducted on beds of aligned carbon nanotubes [10] and various high temperature polymer studies [11][12][13][14][15][16] have also demonstrated behavior that is well fit by an activated process at the macroscale.…”
Section: Introductionmentioning
confidence: 78%
“…Michael et al [1], Theiler et al [2], and Hubner et al [3] compared results of ambient lab air testing with those of test submerged in cryogenic liquids and have shown either no trend or trends of reduced friction at cryogenic temperatures. Recent constant environment macroscale studies of various solid lubricants [4][5][6][7], and atomic-scale studies with terraces of graphite [8] show consistent trends of increased friction with decreased temperature, and the notion of thermally activated friction has been proposed [4,8,9]. Variable temperature experiments conducted on beds of aligned carbon nanotubes [10] and various high temperature polymer studies [11][12][13][14][15][16] have also demonstrated behavior that is well fit by an activated process at the macroscale.…”
Section: Introductionmentioning
confidence: 78%
“…A recent molecular scale study of graphite by Zhao et al [16] provided evidence that the temperature dependent friction found for PTFE may be a general result of interfacial sliding. In these studies, an atomic force microscope was used to collect friction data on molecularly smooth terraces of graphite over a temperature range from 140 to 750 K at a vacuum level of 2 · 10 -10 torr.…”
Section: Introductionmentioning
confidence: 99%
“…The friction coefficient increased with decreasing temperature, and the data collected followed an Arrhenius dependence with an activation energy of E a = 9.6 kJ/mol. The molecular scale experiments by Zhao et al [16] addressed many of the uncertainties raised in the macroscopic experiments conducted by McCook et al [4]; namely, the sliding interface was well-characterized, interfacial sliding was confirmed, and the experiments were run in ultra-high-vacuum at temperatures well above the temperature for equilibrium ice formation on the surfaces (frost-point).…”
Section: Introductionmentioning
confidence: 99%
“…Since loading forces can be kept very low, effects such as wear and plastic deformation can be prevented in most cases. Measurements have been performed as a function of a wide variety of parameters, such as the externally applied cantilever load F L , [7-10, 18, 19] the sliding velocity, [11,17,20] the tip radius and shape, [7,9,10] the relative orientation between scan direction and substrate lattice, [21][22][23][24] the temperature, [25,26] or the chemical nature of the sample. [27][28][29] These features undoubtedly made FFM a powerful tool for nanotribological studies.…”
Section: From Friction Force Microscopy To Nanoparticle Manipulationmentioning
confidence: 99%